(untitled) (Bulletin of Innovative Research, 2026)
This article analyzes the significance of innovative scientific and practical approaches for the conservation of endangered, including Red Book-listed, medicinal and rare plants in Uzbekistan. Field surveys and GIS analyses conducted in the Zomin, Kitob, Chimyon, and Kyzylkum regions revealed a significant decline in the populations of Ferula, Astragalus, Tulipa, and Iris species over the past 10–15 years. The study also emphasizes that the lack of fully established seed banks and genetic monitoring systems in Uzbekistan poses a risk to the stability of the gene pool. Innovative approaches—microclonal propagation, ex-situ conservation, drone monitoring, digital population mapping, and the use of bioindicators—are proposed as key tools to enhance the efficiency of rare plant conservation